Efektivitas Efektivitas Media Pembelajaran Augmented Reality Materi Bangun Ruang Sisi Datar di SMPN 1 Gunungsari - Hasanah, Wirda; Harry Soeprianto; Baidowi; sripatmi (FKIP Universitas Mataram, 2025)
This study aims to determine the effectiveness of Augmented Reality (AR)-based learning media on students' mathematics learning outcomes of flat-sided space building material. This research uses a quasi-experiment method with a non-equivalent control group design. The subjects of this study were VII grade students of SMP Negeri 1 Gunungsari as many as two classes, namely the experimental class and the control class. Where the experimental class is given Augmented Reality-based learning media while the control class is given website-based learning media. This study was conducted for 5 meetings, starting with giving a pretest, followed by learning by implementing learning media for 3 meetings in each class and giving a questionnaire of learning interest for the experimental class. The last meeting was held posttest to determine student learning outcomes. Data analysis used independent sample t-test and N-Gain Mean analysis. The results showed that AR media was significantly effective in improving students' math learning outcomes (P < 0.005), with the N-Gain category of the experimental class classified as high and effective, while the control class was categorized as less effective. In addition, the use of AR media also increases students' interest in learning, with a very good category.